Mechano-chemical radical formation and polymerization initiation during wet grinding of alumina - Damm, Cornelia; Peukert, Wolfgang (Journal of Colloid and Interface Science, 2011)
The formation of free radicals during wet grinding of alumina in a stirred media mill was studied by using the test radical 2,2-diphenyl-1-picrylhydracyl (DPPH). The kinetics of mechano-chemical radical formation follows a zeroth-order rate law. Particle breakage as well as mechanical activation of the surface of the alumina particles contributes to the radical formation. The rate constants of the radical formation due to mechanical activation of the particle surface k and due to particle breakage k depend on the milling process parameters. The radical formation during wet grinding of alumina was exploited to initiate mechano-chemical polymerization reactions of acrylic acid and acryl amide, respectively. In this way nanoparticles functionalized with polyacrylic acid and polyacryl amide, respectively, are obtained. The influence of the milling process parameters on the kinetics of mechano-chemical radical formation and on the grafted amount of polymer is discussed on the basis of stress energy and number of stress events in the mill. A correlation between the grafted amount of polyacryl amide on the alumina particles and the total radical formation rate was found showing that the concentration of mechano-chemically formed free radicals governs the efficacy of a chemical reaction at activated particle surfaces. © 2011 Elsevier Inc.
Keywords: Alumina; Kinetics; Mechano-chemical polymerization; Radical formation; Stirred media mill